Utilization of Tacit and Explicit Knowledge in the New Employee Adaptation Process to Support Organizational Sustainability at PT Modern Plasindo Mutiara - Saut Martua; Vivi Gusrini Rahmadani P; Meilita Tryana Sembiring (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The effective implementation of knowledge management plays a role in improving organizational performance, innovation, and service quality through knowledge transfer between generations of employees. This study aims to analyze the implementation of tacit and explicit knowledge, identify obstacles, and formulate efforts to optimize knowledge management in supporting new employee adjustment and organizational sustainability at PT. Modern Plasindo Mutiara. This study uses a descriptive qualitative approach with primary data sources obtained through interviews and secondary data from various written sources and relevant documentation. The study involved 8 informants selected using purposive sampling techniques based on criteria. Data analysis was conducted using the SECI and Miles–Huberman models to understand the process of knowledge sharing and adaptation of new employees. The results show that the implementation of tacit and explicit knowledge in the adjustment of new employees at PT. Modern Plasindo Mutiara is carried out through a combination of direct experience, informal guidance, and structured documentation and work procedures. The main obstacles to the implementation of both types of knowledge include a suboptimal documentation system, a mismatch between SOPs and field practices, and limited mechanisms for structured experience sharing. Optimizing tacit and explicit knowledge is a strategic step to strengthen the adaptation of new employees and support organizational sustainability, which is carried out through strengthening mentoring, developing a culture of experience sharing, and training based on observation and direct practice so that senior employees’ work experience can be transferred effectively. This study emphasizes the importance of integrating tacit and explicit knowledge in the adaptation of new employees, through the role of mentoring, direct learning, and documentation that aligns with work practices in supporting organizational sustainability.